DEVELOPING ANDROID-BASED TEAM GAMES TOURNAMENT (TGT) TYPE COOPERATIVE LEARNING FOR STUDENTS’ ACADEMIC ACHIEVEMENT IN BIOLOGY - Ilham Hudi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The students were rarely willing to give arguments and answers to the teacher during the learning process because they were not used to complete learning problems by themselves and they were already accustomed to accept all of the explanation from the teachers. This learning process made students to take all of the concepts without potential processing existed in themselves and around them. One way to improve this was by implementing an appropriate learning model as well as by briefly delivering or presenting the materials which collaborated telling or transmission, organizing students’ activities and making learning possible, as well asthe learning problems faced at present. This research aimed to produce the learning model which applied team games tournament method and assisted by Android with a good quality and worthy to be implemented during the learning process. It also aimed to describe how well the quality of the learning model was. This research was conducted by using ADDIE development method. The results indicated that the learning model fulfilled the aspects of validity, practicality, and effectiveness. Based on the score obtained, the material validation = 99, so the validation value = 66. The score of practicality = 98 with a percentage of 78.4% which was in Good category. The learning model was effective if there was an increase in students’ learning outcomes before and after using the model developed. The minimum criteria of learning mastery could be achieved if at least 75% of the total students got a score >70 in increasing learning outcomes.